THE ROLE OF CORONARY BYPASS SURGERY IN REDUCING MORTALITY AND ENHANCING QUALITY OF LIFE AMONG HEART DISEASE PATIENTS - Dr. Adel Moideen; Safiyyah Mukarram Khan; Anurang Rawat; Dr. Roohullah Amin Safi; Preeti Batheja; Indresh Yadav; Mohamad A. Khedari; Tawseef Ahmad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Cardiovascular diseases are a predominant cause of mortality in industrialized nations, contributing to approximately 30% of deaths and imposing substantial economic burdens on healthcare systems. Coronary heart disease, a major contributor to cardiovascular mortality, necessitates effective management strategies to improve patient outcomes and quality of life.Objective: This study aims to assess the role of coronary bypass grafting (CABG) in treating coronary heart disease, evaluating its success rates, complications, and the decision-making process involved in selecting appropriate graft types for individual cases.Methods: We conducted a documentary bibliographic review focusing on the theoretical aspects of coronary bypass surgery. The data collection was primarily executed through electronic databases such as PubMed and Google Scholar, utilizing health sciences descriptors and MESH terms. The collected literature will undergo a thorough review to extract relevant information about the effectiveness and challenges of CABG.Results: Preliminary findings underscore the crucial role of CABG in reducing mortality rates, extending patient longevity, and enhancing the quality of life for those suffering from coronary heart disease. Despite the complexity and risks associated with the surgical procedure, the success rate remains high. The choice of graft type, a critical component of the surgical strategy, varies based on individual patient conditions and has significant implications for outcomes.Conclusion: Coronary bypass grafting stands as a pivotal intervention in cardiovascular medicine, especially for managing severe coronary heart disease. While the procedure is technically demanding and associated with various challenges, its high success rate and the significant improvement in patient outcomes justify its continued use as a treatment modality. Future research should focus on optimizing graft selection processes and minimizing surgical risks to enhance patient outcomes further.